Planning for Solar Energy as an Energy Option for Palestine - Mai Fawaz Fayaz Abu-Hafeetha (My University, 2009)
The energy sources in the Palestinian territories are very limited and It depends on the imports of different types of fuel from neighboring countries, especially Israel, as the energy consumption in all sectors in the Palestinian territories is relatively small compared with the neighboring Arab countries, as well as the highest percentage of energy consumption is in the household sector, followed by The transportation sector, the third is the industrial sector which has a few percentage of energy consumption. The researcher in this study studied the energy sector in the Palestinian territories in terms of the quantity of energy consumption in all sectors (domestic, industrial commercial ...), studied all types of available fuels and their prices. The solar energy and its potential in the Palestinian territories were studied in terms of the amount of incident radiation during the year and the various possible applications, and the projects that have been implemented in various regions. In this study, a hierarchic system was used for planning of the energy sector in Palestine with maximum possible usage of solar energy as an indigenous, clean and cheap source of energy. This hierarch system includes all solar system technologies that can be applied to the in various sectors. The analysis have shown that solar energy share can reach 11.4% of total energy consumption for the year of 2020 just by implementing solar thermal systems; passive and active. This share may exceed 18% if power generation was implemented using concentrated thermal systems in West Bank and Gaza. The planning process of expected saving percentage in energy consumption in the Palestinian territories is not easy, for many reasons such as economic, demographic, and political. The researcher adopted on the variables of population and construction in order to forecast the percentage of savings in energy consumption for the coming years in various sectors. As an expected result, the reduction in consumption of fossil fuels by increasing solar share will have positive environmental impacts as well as economical impact. Gas emission, mainly CO2 will be reduced sharply if this plan is implemented in Palestine.

إن مصادر الطاقة في الأراضي الفلسطينية محدودة جدا والاعتماد الأكبر على استيراد أنواع مختلفة من الوقود من الدول المجاورة خاصة إسرائيل, كما إن استهلاك الطاقة في جميع القطاعات في الأراضي الفلسطينية صغير نسبيا مقارنة مع الدول العربية المجاورة, كذلك إن أعلى نسبة لاستهلاك الطاقة يوجد في القطاع المنزلي يليه قطاع المواصلات أما القطاع الصناعي فنسبة الاستهلاك فيه قليلة. قامت الباحثة في هذه الدراسة بدراسة قطاع الطاقة في الأراضي الفلسطينية من حيث كمية الاستهلاك في كافة القطاعات( المنزلي الصناعي التجاري) ودراسة أسعار الوقود لسنوات مختلفة مع بيان أسباب ارتفاعها. كذلك تم دراسة الطاقة الشمسية ووضعها في الأراضي الفلسطينية من حيث كمية الإشعاع الساقط عليها خلال السنة وتطبيقاتها المختلفة, والمشاريع التي تم تنفيذها في مختلف المناطق. تم خلال هذه الدراسة التعرف إلى التطبيقات الممكنة للطاقة الشمسية في مختلف القطاعات أهمها الصناعة والذي يفتقر إلى أي تطبيق للأنظمة الشمسية كحالة تخطيطية للمستقبل, وبناء على استخدام هذه التطبيقات فانه تم توقع نسبة الطاقة التي يمكن توفيرها عند استخدام الطاقة الشمسية بالشكل الأمثل من مجموع الطاقة الكلي المستهلكة للعام 2020 والتي تبلغ 11.4% إن عملية توقع نسبة التوفير في استهلاك الطاقة في الأراضي الفلسطينية ليست سهلة وذلك لأسباب اقتصادية وسكانية وسياسية, ولقد اعتمدت الباحثة على المتغيرات السكانية والإنشائية وذلك من اجل توقع نسبة التوفير في استهلاك الطاقة للأعوام القادمة في مختلف القطاعات. بعد مقارنة النتائج المتوقعة عند تطبيق الأنظمة الشمسية في مختلف القطاعات وكمية الطاقة المستهلكة حاليا وبدون تطبيق لهذه الأنظمة تبين أن هناك توفير بنسبة 11.4% من مجمل الطاقة المستهلكة في فلسطين وقد تصل هذه النسبة إلى 18% في غزة وأريحا عند تطبيق مشاريع توليد الطاقة الكهربائية عن طريق الشمس. وكنتيجة متوقعة في تقليل نسبة استهلاك الطاقة مما يعني تحقيق جدوى اقتصادية ليس هذا وحسب بل ما يترتب على ذلك من فائدة للبيئة حيث إن الأنظمة الشمسية والطاقة الشمسية هي أصدقاء للبيئة لمميزاتها في تقليل نسبة انبعاث غاز CO2.
تخطيط الطاقة الشمسية كمصدر بديل للطاقة في فلسطين